2021
DOI: 10.5539/jas.v14n1p1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Row Spacing and Plant Density on the Yield of Faba bean L. Under Very Differentiated Humidity Conditions

Abstract: The research covered Polish low-tannin Faba bean ‘Albus’, and its yielding depending on the row spacing and plant density under very different humidity conditions across the research years. The mean multi-year faba bean seed yield was 4.01 t ha-1 and it was most correlated with the total rainfall in August and in June-August. Due to a considerable variation in the total rainfall and air temperature, the faba bean seed yield ranged from 0.69-2.14 t ha-1 in dry years (2018-2019) with high air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
2
0
0
Order By: Relevance
“…Stated differently, the optimal plant density in terms of the number of shoots per plant in both seasons was found to be 20 kg/fed. The present results is confirmed with those obtained by [28][29][30][31][32][33][34].…”
Section: Control =Normal Irrigation (Four Irrigations As a Controlsupporting
confidence: 93%
“…Stated differently, the optimal plant density in terms of the number of shoots per plant in both seasons was found to be 20 kg/fed. The present results is confirmed with those obtained by [28][29][30][31][32][33][34].…”
Section: Control =Normal Irrigation (Four Irrigations As a Controlsupporting
confidence: 93%
“…The reason for the decrease is due to the increase in the number of plants per unit area and thus the increase in competition between the crop plants for light and nutrients, which led to a decrease in the chlorophyll index in the leaves (Table 3), and their low efficiency in absorbing light, and then the decrease in the effectiveness of photosynthesis and the transmission of its products to the emerging flowers, which reduced the proportion of fruit set in them and thus the decrease in the number of pods in the plant. This result agrees with [11][12][13][14], they found that higher plant densities resulted in fewer pods per plant. No statistically significant interaction was found between the study parameters and this characteristic, either.…”
Section: Number Of Pods Per Plant (Pod Plant -1 )supporting
confidence: 91%
“…The planting population of crops is important for large-grained seed varieties and it has been recognized as the main determinant of crop yield (Janusz, 2022). Optimal plant density (that is, the smallest population that produces the highest yield) and the appropriate design of plants per area allow crops to use resources in the best way and produce maximum grain yields (Kebede, 2020).…”
Section: Introductionmentioning
confidence: 99%